Zagospodarowanie odpadów w systemie zintegrowanym - Walenciak, Dorota (Waste Development in Integrated System, 2007)
At this article a conception was presented of waste development in the integrated system. Such a conception is an optimal solution is embracing the integrated waste disposal which is starting from action making the amount of waste smaller ecological and economic justified elements of the meeting and using the recyclable waste, directed processing and the waste segregation and is ending with processing remained remnant waste indifferent, being fit for ultimate storing figure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 601-608